A QoS‐aware service discovery method for elastic cloud computing in an unstructured peer‐to‐peer network. (19th February 2013) - Lin, Wenmin; Dou, Wanchun; Xu, Zhanyang; Chen, Jinjun; Chen, Jinjun; Ranjan, Rajiv
SUMMARY Traditionally, service discovery is often promoted by the centralized approach that typically suffers from single point of failure, poor reliability, poor scalability, to name a few. In view of this challenge, a QoS‐aware service discovery method is investigated for elastic cloud computing in an unstructured peer‐to‐peer network in this paper. Concretely speaking, the method is deployed by two phases, that is, service registering phase and service discovery phase. More specifically, for a peer node engaged in the unstructured peer‐to‐peer network, it firstly registers its functional and nonfunctional information to its neighbors in a flooding way. With the multiple registered information, the QoS‐aware service discovery is promoted in a probabilistic flooding way according to the network traffic. At last, extensive simulations are conducted to evaluate the feasibility of our method. Copyright © 2013 John Wiley & Sons, Ltd.